How to break a sperm whale’s teeth: dental damage in a large Miocene physeteroid from the North Sea Basin - Lambert O.; Bianucci G. (Journal of Vertebrate Paleontology, 2019)
In contrast to the suction-feeding, predominantly teuthophagous extant sperm whale, several Miocene physeteroids display proportionally larger teeth, deeply embedded in both upper and lower jaws. Together with other osteological features, these differences lead to the functional interpretation of these taxa as macroraptorial predators, using their teeth to capture and process large marine vertebrates. However, the assumption that strong forces applied to macroraptorial physeteroid teeth during powerful bites and contacts with bone material should result in major dental damage has not yet been tested. In the present work, we analyzed a large collection of physeteroid teeth with an enameled crown from the Miocene of the North Sea Basin. We especially focused on a set of 45 teeth of Scaldicetus caretti discovered in Antwerp (Belgium, southern North Sea Basin) and tentatively dated to the Tortonian (early late Miocene). Visual inspection and computed tomography (CT) scans revealed dental damage, including wear and breaks. The latter could be interpreted as chipping fractures, occurring along the crown, and vertical root fractures, observed along the apical part of the massive root. Chipping fractures are most likely due to contacts with hard material, whereas vertical root fractures may result from the application of strong and repetitive bite forces and/or contacts with hard material. Such results further support the interpretation of a series of Miocene physeteroids with proportionally large teeth as macroraptorial (rather than suction-feeding) top predators. Considering the size of the teeth of S. caretti, its most likely prey items were other large marine vertebrates.